Butterfly Constrained Optimizer for Constrained Optimization Problems - Kumar A.; Maini T.; Kumar Misra R.; Singh D. (My University, 2025)
An extension of the new optimization algorithm, butterfly optimizer (BO) for the constrained optimization problem is discussed in this paper. This version of BO is called butterfly constrained optimizer (BCO) which mimics the mate-locating behaviors of male butterfly and his behavior toward sunspots. In BCO, the location of male butterflies presents the trial solutions, and sunspots and dark-spots represent the feasible and infeasible region of search space. Two major mate-locating behaviors, patrolling and perching, are applied to generate new location of butterflies toward the feasible reason of search space to optimize the problem without violating any constraints. In this paper, five benchmark constrained optimization problems are considered to analyze the performance of BCO, and the benchmark results are compared with well-known state-of-the-art constrained techniques. Comparative result shows that the performance of BCO concerning its optimization capability, efficiency, and accuracy is better than other. © 2019, Springer Nature Singapore Pte Ltd.